Impacts of phosphoric acid / hydrogen peroxide addition on metals and organic content of sludge - Tatar, Şule Yüksel; Öbek, Erdal; Hasar, Halil (My University, 2007)
In this study, the removal of heavy metals from sludge in a municipal treatment plant was investigated by using different volumes and concentrations of phosphoric acid, both with and without hydrogen peroxide. The level of inorganic and organic matter was firstly measured in the residual sludge cake. The most effective removal of heavy metals was obtained by a 40-ml treatment with H3PO4 in different concentrations for each corresponding metal, generally 35% H3PO4. The results indicate that there is a relationship between the removal of heavy metals and the solution pH. This study's test results show that treatment applications - both with and without H2O2 - did not change the organic matter value of the sludge cake. © by PSP.
Keywords: Biological sludge; Heavy metals; Organic matter; Phosphoric acid